An unambiguous moving target imaging method for maritime surveillance in high-resolution wide-swath mode. Issue 8 (2nd August 2020) - Jia, Xinlin; Song, Hongjun; Fan, Huaitao; He, Wenjing
ABSTRACT: Multichannel synthetic aperture radar (SAR) is an effective method to achieve high-resolution wide-swath (HRWS) imaging simultaneously. Many algorithms have been proposed to reconstruct stationary targets. However, moving targets cannot be well reconstructed through traditional reconstruct algorithm for static scenes and the ghost targets of the moving targets will have a great influence on SAR image interpretation, especially in maritime scenes. This paper proposed an unambitious imaging method for moving targets in maritime scenes. Firstly, the slant-range velocity of the moving target is estimated through maximizing the minimum variance distortionless response (MVDR) beamformer output in the image domain. Secondly, the phase introduced by the slant-range velocity is compensated before reconstruction. Finally, the Chirp Scaling (CS) algorithm is used to image the full scene and the moving targets can be refocused separately after image formation. The proposed method has the advantage of estimating the slant-range velocity without search or redundant channels. The performance of the proposed method is verified by simulation experiments and real data of Chinese Gaofen-3 (GF-3) SAR sensor.